Tecnologias, desempenho financeiro e transformações na profissão contábil: um estudo nos escritórios de contabilidade da Região Nordeste do Brasil - Santos, Marcos Igor da Costa (2020)
This thesis aimed to analyze technology as a factor of changes in the accounting profession and its relationship with financial performance, based on the understanding of managers of accounting offices in the Northeast region of Brazil. Therefore it was necessary to identify practices that are developed in an automated way; develop an index to identify the automated sectors; know the types of technological information tools used; develop an index to measure the use of information technology tools; and, check the level of willingness for managers to change regarding technology. The research universe considered 10.873 offices registered with the Regional Accounting Councils (CRC) and the sample involved 2.359 offices, identified through the internet. Data collection involved the application of a questionnaire that contained 23 open and closed questions and which was sent to the offices through their respective emails during the period from 10.06.2020 to 08.31.2020. Regarding the number of returns, only 406 responses were obtained. For data treatment, two models were developed and to estimate the relationships between the variables, descriptive statistics and the Quantile Regression (RQ) model were used through the Bootstrapping method. The analysis of the data made it possible to describe the profile of the managers, pointing out the predominance of the male gender, mean age of 43 years and graduate academic training Lato Sensu. Regarding the characteristics of the offices, the legal form "Society" predominated, with the main area of activity the "Private" sector, with an average of 47 clients and containing about five employees. The average monthly revenue found was over R$ 52,000.00 and the average investment in technology totaled approximately R$ 3,700.00. The results showed that, in the two models proposed, the use of technological tools positively affected the financial performance of the offices and proved that the higher the level of automation of the offices, the greater the financial performance. Regarding the level of willingness to change in relation to ICT, divergent results were observed in relation to the two models analyzed, considering that in model 1 this variable had a negative impact on revenue, while in model 2 it affected positively on profitability over investments in technology. The number of employees proved to be a variable that interferes with the adoption of technological resources and financial performance, given that the evolution of technology is promoting changes in the role of the accounting professional and there was a positive effect on both models. The other variables belonging to the construct presented conflicting results. Finally, it was concluded that the research hypothesis can be accepted, since the managers of accounting firms that are more open to change in the face of technology, make greater use of informational technological tools and have a greater financial performance. In addition, these results demonstrated the applicability of the contingency theory and cognitive dissonance, indicating that there is a dependency of the organization in relation to its environment and the technology adopted, and there is no dissonant behavior among the ideas pointed out by the respondents.